A study of the non-auditory effects due to noise exposure among airport workers / Nor Liyana Man - Man, Nor Liyana (2011)
Noise can be defined as unwanted sound. Sound is responded in a different way and subjectively by people. Effects of noise can be dividing into two, auditory and non auditory effects. Auditory effects related to hearing loss and non-auditory effects related to physiological effects and psychological effects. The study was conducted at Sultan Ismail Petra Airport, Kota Bahru, Kelantan. Respondents in study group were selected at two different locations such as fire station and engineering area. The study design of this study is cross-sectional study. Sampling data collection has been done by using Sound level meter, Dosimeter, Automatic Sphygmomanometer, questionnaires, Digital camera, oral interview and observation. A statistical analysis that is statistical package for the social science (SPSS) version 16.0 was used in this study. The study was found that the highest environmental noise level comes from aircraft engines (136.3 dB(A)]. Then, workers at engineering area was recorded highest level of noise exposure computed in 8-hours period, 92.3dB (A). Log data analysis at study group is 91.1 dB(A) while at control group is 71.2 dB(A) . For the measurement of blood pressure (BP), the mean of systolic blood pressure after work is 135.53mmHg while the mean of diastolic blood pressure after work is 90. 70mmHg. Statistical analysis showed that there is significant association *(p-value <0.05) between high noise level and increase in BP. Resijlt also showed that there is significant association *(p-value <0.05) between high noise level and other non-auditory effects such as ringing, headache, anxiety and emotional disturbance. In conclusion, there is a significant association between high noise level and non-auditory effects of noise.